MENGEMBANGKAN KEMAMPUAN PEMAHAMAN, KONEKSI DAN KOMUNIKASI MATEMATIS SERTA KEMANDIRIAN BELAJAR MATEMATIKA SISWA SMP MELALUI RECIPROCAL TEACHING - QOHAR, Abdul (2010)
The main problem of this study is how the development of mathematical understanding ability, mathematical connection, mathematical communication and mathematics self-regulated learning are reviewed on the basis of learning approaches, school level and initial ability in mathematics. This research is quasi experimental by the static group comparison design. Experimental group was treated under reciprocal teaching, while control group was under conventional teaching model. The study involved 254 of 9th grade secondary school students in the district of Bojonegoro, East Java, representing high, middle and low level schools. Data analysis in terms of hypothesis testing adopted two way Anova and t-test. The findings show that: (1) students taught in reciprocal teaching approach were better in understanding, connection, communication and mathematics self regulated learning than those in based on all school levels and initial ability in mathematics, but at high level school, the improvement is not significant; (2) there is a significant interaction between models of learning and school level to mathematical understanding, mathematical connection and mathematical communication of student; (3) there is no significant interaction between models of learning and initial ability of mathematics to mathematical understanding, mathematical connection, mathematical communication and mathematics self regulated learning. Besides those findings, the study also found association between mathematical understanding and connection, between mathematical understanding and communication, between mathematical understanding and self regulated learning, between mathematical connection and communication, between mathematical connection and self regulated learning, and between mathematical communication and self regulated learning.